A Compact 5G Decoupling MIMO Antenna Based on Split-Ring Resonators. (2nd June 2019) - Xu, Ziyu; Zhang, Qisheng; Guo, Linyan
Abstract : A compact planar multiple-input multiple-output (MIMO) antenna array for 5G band is proposed in this paper. To improve the isolation of compact microstrip antenna array, this paper mainly presents an electromagnetic resonant ring method for MIMO antenna array. The proposed antenna can cover both the 3.3-3.6 GHz and 4.8-5 GHz bands proposed for the 5G band. The antenna proposed in this paper consists of two symmetrical meandered monopole radiators, grid structures, and a Y-shape element. Two different sizes of split-ring resonators (SRRs) are used to suppress the interference of the coupled signal to the antenna system; thereby it can reduce the mutual coupling effect. The experimental results show that the mutual coupling between the two elements is below -25 dB in both of the bands after adding the SRRs. And this antenna is only 23×19 mm 2 . Its compact size and structure can be used as a mobile terminal antenna.